The Strategic Potential of Community‐Based Hybrid Models: The Case of Global Business Services in Africa. (February 2017) - Manning, Stephan; Kannothra, Chacko G.; Wissman‐Weber, Nichole K.
Abstract : Research Summary: Firms in latecomer economies, such as Sub‐Saharan Africa, often have limited success with traditional business models. We explain why it can be more feasible to adopt a hybrid model in such a region that combines profitability with serving local communities, e.g., by promoting inclusive employment or by targeting underserved markets. Sub‐Saharan Africa supports hybrid models and social enterprises mainly through local community resources (e.g., labor, market ideas), community organizations giving access to such resources, and experience with business‐community alliances. Hybrid models can benefit from such conditions when business clients and governments support the social mission and when firms are ready to target niche rather than mainstream markets. We illustrate the business potential of hybrid enterprises based on the case of 'impact sourcing' in global business services in Kenya and South Africa. Managerial summary: As a latecomer economy, Africa faces persistent difficulties with catching up in global markets. This study examines the strategic potential of community‐based hybrid models, which balance market profitability with social impact in local communities. Focusing on the global business services industry in Kenya and South Africa and the practice of 'impact sourcing' (the hiring and training of disadvantaged staff servicing business clients), we find that while regular providers struggle to compete with global peers, hybrid model adopters manage to access underutilized labor pools through community organizations, and target less competitive niche client markets. We further identify key industry‐, institutional‐, and firm‐level factors that affect hybrid model adoption. Findings have important implications for research on catch‐up processes in latecomer economies, hybrid models, and global business services. Copyright © 2016 John Wiley & Sons, Ltd.